Cover Image. Issue 3 (March 2017) - Fikree, A.; Aktar, R.; Morris, J. K.; Grahame, R.; Knowles, C. H.; Aziz, Q.
Abstract : The cover image, created by Faaria Khan and Dania Khan, is based on the Original article, The association between Ehlers‐Danlos syndrome—hypermobility type and gastrointestinal symptoms in university students: a cross‐sectional study, byQASIM AZIZ et al., DOI10.1111/nmo.12942 .